Sinter-joining of W-10Ti powder to W-10Ti waste target by spark plasma sintering. (June 2021) - Huang, Lei; Pan, Yafei; Zhang, Jiuxing; Xu, Wenfei; Du, Yong; Zhang, Yuhui; Zhang, Shuyan
Highlights: W-10Ti powders and W-10Ti waste target were sintered and joined by SPS. The effects of joining temperature and time for the joints were investigated. The mechanism assisted by SPS during the sinter-joining process was studied. Abstract: Spark plasma sintering (SPS) technology has been applied to the sinter-joining of W-10Ti powders and W-10Ti waste targets. The effects of joining temperature (1200–1600 °C) and time (5–20 min) on the microstructure evolution and mechanical properties were studied systematically. The microstructural observation results indicated that the joining temperature and time had a significant effect on the number of βTi(W) phase and grain size. There was little difference in the distribution of relative density and hardness between the powder-sintered body and waste target. The bending strength of the original waste target and regenerated target (1500 °C/5 min) was 660.32 ± 18.94 MPa and 455.30 ± 15.12 MPa, indicating that the powder-sintered body and the waste target achieved a good joining when the temperature was 1500 °C and the time was 5 min. A regenerated W-10Ti target with reliable interface joining, high density, less βTi(W) phase and small grain size was obtained at the joining temperature of 1500 °C and the dwelling time of 5 min. EBSD results at 1500 °C/5 min suggested that the grain boundary diffusion induced the formation of wedge-shaped triple junctions and that a reconstruction behavior occurred at the interface. A schematic diagram was established to characterize the mechanism of the interface formation and evolution. The series of sinter-joining processes assisted by SPS technology are considered to involve pressure welding, micro-arc welding, resistance welding and diffusion welding, which can provide experimental reference and theoretical guidance for repairing the W-10Ti waste target with SPS technology.